Efficacy and safety of Saccharomyces boulardii as adjunct therapy with Vancomycin in treating Clostridioides difficile infection: A randomized controlled trial - Taned Chitapanarux; Umaporn Wiracha; Poramed Winichakoon; Parichat Salee; Patrinee Traisathit (Scientific Reports)
Abstract Clostridioides difficile infection (CDI) is a significant cause of hospital-acquired diarrhea, leading to high morbidity, recurrence, and healthcare costs. Probiotics like Saccharomyces boulardii show potential as an adjunct therapy to standard CDI treatment, but further trials are needed to confirm their efficacy. This study assessed the efficacy and safety of S. boulardii combined with vancomycin for treating mild to moderate CDI. 120 CDI patients diagnosed with positive stool toxin test were randomly assigned to receive two capsules of 250 mg of S. boulardii or a placebo every 12 h alongside 125 mg of vancomycin every 6 h for 10 days. The primary endpoint was the clinical cure rate, with secondary endpoints including recurrence, global cure rate, and diarrheal outcomes. Clinical cure rates were similar between groups (98.4% vs. 98.3%), but the combination group had a significantly higher global cure rate (96.6% vs. 85.3%, p = 0.044) and lower recurrence rate (1.7% vs. 13.1%, p = 0.032). No significant differences were found in diarrheal outcomes, functional ability, or adverse events. No patients discontinued treatment due to intolerance. In conclusion, adding S. boulardii to vancomycin reduced CDI recurrence without affecting functional recovery or increasing adverse events.